PENINGKATAN FOKUS BELAJAR SISWA MELALUI PENDAMPINGAN DAN OBSERVASI KELAS DI SD III LUOK MANIPI - Anastasya Bupu Astin; Mustakim Mustakim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Students' ability to maintain focus on learning is a crucial factor in the success of the elementary school learning process. This community service program aims to improve student learning focus through mentoring and classroom observation activities at Luok Manipi Elementary School. The program is implemented through several stages, including identifying classroom problems, observing the teaching and learning process, mentoring teachers in the use of varied learning methods, and providing engaging learning support media. Findings from the program indicate that low student learning focus is influenced by classroom conditions, the use of conventional teaching methods, and a lack of visual stimulation and interactive learning activities. Through mentoring and classroom evaluation, there has been an increase in student engagement, attention during learning, and the ability to understand the material. This community service program recommends the development of interactive learning media and ongoing training for teachers as strategies to optimize student learning focus at the elementary school level.